Ultrazvukový staging karcinomu endometria - doporučená metodika vyšetření - Frühauf, F; Dvořák, M; Haaková, L; Hašlík, L; Herboltová, P; Chaloupková, B; Kožnarová, J; Kubešová, B; Lukáčová, I; Marek, R; Neumannová, H; Peschout, R; et al. (Ceska gynekologie, 2014)
The extent of the staging surgery in cases of histologically proven endometrial cancer depends on whether the tumor is of high risk or low risk for extrauterine spread and recurrence. There are several significant prognostic factors - histological subtype and grade of dediferentiation from preoperative biopsy and local stage of uterine involvement based on imaging methods. The depth of myometrial invasion and presence of cervical stromal infiltration (local staging) can be assessed by ultrasound with the overall accuracy comparable to that of magnetic resonance. Transvaginal ultrasound enables to vizualize detailed pelvic anatomy and that is why it is considered to be a suitable tool for assessment of local stage of endometrial cancer. It is advisable to use the standardized terminology defined by International Endometrial Tumor Analysis group (IETA) to describe ultrasound findings. The standardized methodology of ultrasound preoperative staging examination based on prearranged protocols is recommended.
Keywords: směrnice pro lékařskou praxi jako téma; invazivní růst nádoru; Practice Guidelines as Topic; předoperační péče; lokální recidiva nádoru; Preoperative Care; staging nádorů; lidé; Neoplasm Recurrence, Local; Endometrial Neoplasms; Ultrasonography; Neoplasm Staging; ženské pohlaví; Humans; Neoplasm Invasiveness; Female; nádory endometria; ultrasonografie